2017
DOI: 10.1038/srep41337
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates myocardial ischemia/reperfusion injury in type 1 diabetic rats by preserving mitochondrial function: role of AMPK-PGC-1α-SIRT3 signaling

Abstract: Enhancing mitochondrial biogenesis and reducing mitochondrial oxidative stress have emerged as crucial therapeutic strategies to ameliorate diabetic myocardial ischemia/reperfusion (MI/R) injury. Melatonin has been reported to be a safe and potent cardioprotective agent. However, its role on mitochondrial biogenesis or reactive oxygen species (ROS) production in type 1 diabetic myocardium and the underlying mechanisms remain unknown. We hypothesize that melatonin ameliorates MI/R injury in type 1 diabetic rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 56 publications
12
147
1
1
Order By: Relevance
“…It is reported that chronic hypoxia could improve the glucose tolerance by activating the AMPK pathway in skeletal muscle [14]. Our study showed that AMPK, especially p-AMPK protein expressions were increased in cardiomyocytes after CIHH treatment, compared with CON cardiomyocytes (p<0.01, Fig.…”
Section: Phosphorylation Of Ampk Is Critically Involved In Regulationsupporting
confidence: 56%
“…It is reported that chronic hypoxia could improve the glucose tolerance by activating the AMPK pathway in skeletal muscle [14]. Our study showed that AMPK, especially p-AMPK protein expressions were increased in cardiomyocytes after CIHH treatment, compared with CON cardiomyocytes (p<0.01, Fig.…”
Section: Phosphorylation Of Ampk Is Critically Involved In Regulationsupporting
confidence: 56%
“…This is referred to as radical avoidance . Melatonin’s indirect anti‐oxidative effects were mediated through various intracellular signalling pathways, including Janus kinase 2/signal transducers and activators of transcription 3 (JAK2/STAT3), nitric oxide synthase (NOS), Silent information regulator 1 (SIRT1) . In addition, melatonin induces AMP‐activated protein kinase (AMPK) phosphorylation and activation in hepatic cells .…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3 serves as a downstream target of AMPK‐activated peroxisome proliferator‐activated receptor (PPARγ) coactivator‐1α (AMPK‐PGC‐1α) signalling, which plays a key role in the regulation of mitochondrial biogenesis and the deacetylation of mitochondrial anti‐oxidative enzymes. It was found that AMPK‐PGC‐1α‐SIRT3 signalling is important in melatonin cardioprotective actions …”
Section: Discussionmentioning
confidence: 99%
“…However, it is of particular interest with regard to free radical generation and resulting consequences for inflammation. While no consistent effects of melatonin have been observed to date in the cases of SIRT2 and SIRT6, upregulation of SIRT3 by melatonin has been reported a couple of times, including conditions of enhanced oxidative stress and inflammation …”
Section: Downstream Factors Of Melatonin's Actions With Relevance Tomentioning
confidence: 97%